They are looking for the oscillation in position back and forth about the equilibrium point.
I guess you could use potential energy converting to kinetic energy and back,
since kinetic energy = 1/2V^2 this could give you the velocity...
But the force=mass times acceleration route (as used by HallsOfIvy) seems much easier.
we know that f=k.x
Where:
f=force, x=displacement, k=spring constant.
from f=m.a and f=k.x, you have: a.m = k.x
Where
a=acceleration, m=mass, x=displacement, k=spring constant.
The complication is that the force (and thus the acceleration) changes with the amount of displacement.
Note that HallsOfIvy has used -k, this is to make the acceleration negative when the displacement is positive,
so the acceleration is acting in the opposite direction to the displacement, to __reduce__ the stretch of the spring.
__________________
~\o/~
*
Last edited by Woody; Dec 18th 2017 at 03:19 PM.
* |